Beyond the IMF - Kapur, Devesh (UN New YorkUS, 2007)
Focuses on the insurance role of the Fund and argues that developing countries are adopting alternative insurance mechanisms, from a higher level of reserves to regional co-insurance facilities to remittances as a counter-cyclical source of foreign exchange.